Synthesis of Substituted Pyrazoles from Aryl-sydnones - Oumessaoud, Asmaa; Akhramez, Soufiane; Bouali, Jamila; Yassine, Hasna; Hamri, Salha; Ouchetto, Hajiba; Hafid, Abderrafia; Pujol, Maria D.; Khouili, Mostafa (Current Organic Synthesis, 2023)
Background: In this current work, a new synthesis strategy was developed to obtain 1,3,4-trisubstituted pyrazoles derivatives. Methods: A series of 1,3,4-trisubstituted pyrazoles have been prepared via 1,3-dipolar cycloaddition reaction of 3-phenylsydnones with a variety of alkenes derivatives, symmetric and non-symmetric alkynes derivatives, N-phenyl-maleimide, N-benzylmaleimides, and maleic anhydride under conventional manner. Results: Moreover, in this work, it has been demonstrated that the 4-bromopyrazole intermediates can be further functionalized by a combination of Suzuki-Miyaura crosscoupling reactions with aryl-boronic acids and N-arylation reactions of anilines. Conclusion: In summary, we have developed a new method to obtain 1,3,4 triarylated pyrazoles through 3-phenylsydnone 1,3-dipolar cycloadditions. By comparing the different reactions, it is apparent that high temperatures and xylene as solvent are key to achieving pyrazoles derivatives. The best yields were observed for symmetric and non-symmetric alkynes as dipolarophiles.
Keywords: C-arylation